THE USE OF ANIMATED VIDEOS IN IMPROVING STUDENTS LISTENING SKILLS AT SMP NEGERI 8 SATU ATAP TONDANO - Haluruk, Lia Sintia; Liando, Nihta V. F.; Sabudu, Delli (Program Studi Pendidikan Bahasa Inggris, 2024)
This research aims to determine the use of animated videos in improving students. This research used a pre-experimental design with one group pretest-posttest design. This research was carried out at SMP Negeri 8 Satu Atap Tondano. The research sample was class VIII, of 15 students, the research instrument given was a pretest and posttest, with 20 questions. The research results shows that the use of animated videos can improve students listening skills, this statement is proven by the students posttest average score (81.66) with a standard deviation of 11.07 which is greater than the pretest average score (41.33) with a standard deviation of 8.11. Apart from that, the results of the hypothesis test shows that the t-test value (3.713) is greater than the t-table (2.144). Therefore, it can be concluded that the use of animated videos can improve the students English listening skills in SMP Negeri 8 Satu Atap Tondano.